Pieter Bruegel the Elder : religious art for the urban community - Kaminska, Barbara A. (Art and Material Culture in Medieval and Renaissance Europe, 2019)
In Pieter Bruegel the Elder: Religious Art for the Urban Community Barbara Kaminska offers the first book-length study of Bruegel's biblical paintings, and argues that they were inherently linked to Antwerp's religious, socio-economic, and cultural transformation.